Perbandingan Gaya Hidup Mahasiswa Urban dan Rural Terhadap Hasil Pembelajaran pada Mahasiswa Fakultas Kedokteran Universitas Prima Indonesia - Wafi Aqilah Yafa; Gusbakti Rusip; Fiska Maya Wardhani (Lembaga Pengembangan Kinerja Dosen, 2023)
A student's lifestyle can be influenced by their studio housing friends, the surrounding environment, local culture, and their level of curiosity. Friends in the boarding house are often the main influence in determining students' daily habits, such as eating patterns, recreational activities, and study habits. Consequently, this research aims to identify requency of exercise, length of study, and type of study between students who live in urban areas and those who live in rural areas and the academic achievements of students at the Faculty of Medicine, Prima Indonesia University. Cross-sectional checks at the Prima University Faculty of Medicine included 60 students. A cross-sectional examination of 60 students from the Faculty of Medicine, Prima Indonesia University was the focus of this research. The variables measured in the research are independent variables, namely the lifestyle of urban students and the lifestyle of rural students, while the dependent variable is learning outcomes seen from the Grade Point Average (GPA). The results of the Spearman rank correlation test show that the relationship between exercise frequency, study duration, study method and total student lifestyle respectively has a p value of 0.043, 0.050, 0.000, and 0.006 < 0.05, consequently it can be concluded that, in part, each student's exercise frequency, study time, study mode and overall lifestyle have a significant relationship with their academic performance. student at Faculty of Medicine, Prima University Indonesia.